PENGARUH CUSTOMER EXPERIENCE, CUSTOMER SATISFACTION, TERHADAP REPURCHASE INTENTION PADA RESTORAN CEPAT SAJI - M. Fadhil Fausta; Patrick Anderson; Renny Risqiani (Universitas Kuningan, 2023)
AbstractTo create Customer Experience, Customer Satisfaction and Repurchase Intention, one of the fast food restaurants in Indonesia presents self-ordering machine technology that allows consumers to order food independently without having to queue at the cashier. The existence of a self-ordering machine is expected to be able to streamline and shorten the time of ordering food at restaurants. This study aims to determine whether self-ordering machines have a positive impact on customer experience, customer satisfaction, and repurchase intention of fast food restaurant customers. This type of research uses hypothesis testing. The sample used is customers who have ordered food at a fast food restaurant using a self-ordering machine which is included in the generation of Y and Z using the Purposive Sampling technique. Data collection used is primary data collected through surveys. This research was conducted using Structural Equation Modeling (SEM) and processed with the help of SPSS and AMOS software. The results of this study indicate that customer experience has a positive and significant impact on customer satisfaction and repurchase intentions on food purchases at fast food restaurants using their ordering machine. Meanwhile, customer satisfaction has no positive and significant effect on repurchase intention. The results of this study can be used as learning for fast food restaurants to increase repurchase intentions at these fast food restaurants. Keywords : Customer Experience; Customer satisfaction; Purchase Intentions; Self ordering MachineAbstrak Dalam rangka menciptakan Customer Experience, Customer Satisfaction dan Repurchase Intention, salah satu restoran makanan cepat saji yang ada di Indonesia menghadirkan teknologi mesin Self Ordering yang membuat konsumen dapat memesan makanan secara sendiri tanpa harus antri dikasir. Adanya mesin Self Ordering ini diharapkan meningkatkan efisiensi terutama dalam mempersingkat waktu pemesananan makanan di restoran. Penelitian ini bertujuan untuk mengetahui apakah mesin Self Ordering memiliki dampak yang positif terhadap Customer Experience, Customer Satisfaction dan Repurchase Intention pelanggan restoran makanan cepat saji. Jenis penelitian ini adalah hipotesis testing. Sampel yang digunakan adalah pelanggan yang pernah memesan makanan di restoran makanan cepat saji dengan menggunakan mesin Self ordering yang termasuk dalam generasi Y dan Z dengan menggunakan teknik Purposive Sampling. pengumpulan data yang digunakan adalah data primer yang dikumpulkan melalui survei. Penelitian ini dilakukan dengan menggunakan Structural Equation Modelling (SEM) dan diolah dengan bantuan Software SPSS dan AMOS. Hasil penelitian ini menunjukkan bahwa Customer Experience memiliki dampak positif dan signifikan terhadap Customer Satisfaction dan Repurchase Intention terhadap pembelian makanan di restoran cepat saji dengan menggunakan mesin Self Ordering. Sedangkan Customer Satisfaction tidak berpengaruh positif dan signifikan terhadap Repurchase Intention. Hasil penelitian ini dapat dijadikan pembelajaran untuk restoran makanan cepat saji agar dapat meningkatkan Repurchase Intention pada restoran makanan cepat saji tersebut. Kata Kunci : Customer Experience; Customer satisfaction; Purchase Intentions; Self ordering Machine